Hepatocellular Carcinoma: Targeted Therapy and Multidisciplinary Care - McMasters, Kelly M. (Springer New York : Imprint: Springer, 2011)
Hepatocellular Carcinoma: Targeted Therapy provides a detailed repository of the latest information regarding HCC epidemiology, diagnosis, imaging, pathology, staging, and treatment options. This volume also provides an up-to-date guide for treatment that explores not only traditional treatments, but newer investigational treatment options including surgical resection, liver transplantation, ablation (radiofrequency, microwave), percutaneous ethanol or acetic acid injection, transarterial chemoembolization (TACE), intra-arterial radiation therapy, and systemic chemotherapy. Heptocellular Carcinoma: Targeted Therapy will be of great value to all health care professionals and trainees worldwide who have an interest in the diagnosis and treatment of HCC, including surgeons, medical oncologists, radiologists, radiation oncologists, and pathologists.